2021
DOI: 10.1021/acssuschemeng.0c08780
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Formation Mechanism of Covalent–Noncovalent Forces Stabilizing Lignin Nanospheres and Their Application in Superhydrophobic and Carbon Materials

Abstract: Self-assembled lignin nanospheres (LNS) have attracted much attention due to the new opportunities provided for the preparation of value-added products derived from lignin. However, the internal connections of the LNS generally depend on weak intermolecular forces, leading to low solubility resistance and thermostability. In this study, we present a simple method for the fabrication of covalent–noncovalent forces stabilizing lignin nanospheres (HT-LNS) through utilizing the natural characteristic that lignin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The result showed that the contact and sliding angles of the prepared coatings were determined to be 151.9 ± 1.4° and 9.4 ± 0.5°, respectively, which could be used as a substitute for non‐environmentally friendly silica nanoparticles. [ 15 ] Paul et al used lignin nanospheres for nano‐spray (LNSR), which exhibited excellent UV‐blocking, antioxidant, and photo‐activated antibacterial properties. [ 16 ] Bai et al used lignin microspheres as Pickering emulsifiers to stabilize oil‐in‐water (O/W) emulsions, which typically showed longer service life compared to surfactant‐based emulsions, as well as enhanced properties of Pickering emulsions such as sunscreen, antioxidants, and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the contact and sliding angles of the prepared coatings were determined to be 151.9 ± 1.4° and 9.4 ± 0.5°, respectively, which could be used as a substitute for non‐environmentally friendly silica nanoparticles. [ 15 ] Paul et al used lignin nanospheres for nano‐spray (LNSR), which exhibited excellent UV‐blocking, antioxidant, and photo‐activated antibacterial properties. [ 16 ] Bai et al used lignin microspheres as Pickering emulsifiers to stabilize oil‐in‐water (O/W) emulsions, which typically showed longer service life compared to surfactant‐based emulsions, as well as enhanced properties of Pickering emulsions such as sunscreen, antioxidants, and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…[12a] Wang et al prepared LNPs with the maximum concentration of 0.4 g L À 1 by tetrahydrofuran/water solvent exchange system. [13] However, the high consumption of solvents and the low concentration of product significantly increased the costs of the production and limited the application of LNPs. Although spray drying and a few cosolvent approaches can prepare LNPs with higher concentrations, [5b,14] the uniformity, stability, and regenerability of LNPs also limited their large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. prepared LNPs with the maximum concentration of 0.4 g L −1 by tetrahydrofuran/water solvent exchange system [13] . However, the high consumption of solvents and the low concentration of product significantly increased the costs of the production and limited the application of LNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin, one of the most abundant renewable bioresources, is a phenylpropane unit-rich amorphous polymer. 1,2 However, the practical application of lignin is way more difficult, owing to its irregular structure with aromatic rings. 3 Aiming at facilitating the application of lignin, various methodologies have been develop in this field; for example, fluorescence lifetime imaging microscopy is used for analyzing the chemical composition of natural lignin 4 and multicopper laccase-mimicking nanozymes of Cu/GMP is developed for lignin degradation.…”
Section: Introductionmentioning
confidence: 99%
“…8 In recent studies, based on the AIE theory the development of fluorescent lignin materials is gaining increasing attention, mainly focusing on the preparation of nanoparticles and nanospheres, which provide opportunities for value-added utilization of lignin. 2,3,[8][9][10][11] In the developed lignin nanomaterials, the aggregated state restricts the intramolecular motions, causing fluorescence emission by blocking the non-radiative decay channel. Meanwhile, for such nanomaterials the following considerations should be noticed: (1) the presence of solvents or polymeric networks is required for the successful fluorescence emission by regulating the assembly state of lignin and other components; otherwise, the aggregation-caused quenching (ACQ) effect would happen; 8,12 (2) the dispersed nanoparticles in solvents are sensitive to temperature, showing poor thermostability of the fluorescent properties at high temperatures.…”
Section: Introductionmentioning
confidence: 99%